Analisis Kebutuhan Bahasa Arab Bagi Pustakawan Institut Agama Islam Negeri Pekalongan - Alghiffary, Muhammad; Nuryani, Nani; Siregar, Nasrun Salim (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This study aims to analyze the need for Arabic for IAIN Pekalongan librarians. There are several main duties and functions of the librarian that directly intersect with the Arabic language. This research is a qualitative research, because the data taken is in the form of written and spoken words. The IAIN Pekalongan Library was used as the locus of research with six librarians as the main informants. The capable method is used to obtain data with fishing rod, record, and record techniques. The data was tested using the completion method at the time of data retrieval. The data is then analyzed using interpretive descriptive methods. The results of this study show that IAIN Pekalongan librarians need Arabic language competence in supporting their performance, namely: collection development, library material processing (classification), and user services in the field of circulation